A comparison of customer preference of standalone retail outlets and stores in shopping malls. (11th April 2022) - Praveena, K.; Soman, Shruthi
The lifestyle of people and the quality of life have seen a tremendous change in the recent past. This has in turn influenced customer preferences and shopping habits. Shopping now has a different dimension than the usual utilitarian one. The hedonic aspect now influences the choice of shopping centres. The stand-alone retail outlets and the shopping malls are finding different ways to attract customers. This study aims to find out the difference in factors that motivate customers in their preference of shopping malls and retail outlets. The findings show that the factors that drive shopping in a shopping mall are entertainment, location, promotional offers, variety, safety and food and beverages while only location, safety and promotional offers drive shopping in retail outlets. The study was conducted in Kerala where the shopping mall culture is yet in the initial stage. Though the majority of the respondents preferred retail outlets to shopping malls, the satisfaction was greater in shopping malls than retail outlets.